Advancements in Data Structures: Bridging the Gap Between Theory and Real-world Applications - Ushaa Eswaran; Vivek Eswaran; Keerthna Murali; Vishal Eswaran (International Journal of Data Structure Studies, 2024)
In the rapidly advancing landscape of computer science, this study unfolds a comprehensive exploration of Data Structures, spanning from foundational principles to cutting-edge innovations. Data structures form the backbone of computational processes, and this study aims to dissect and illuminate their pivotal role. Beginning with fundamental concepts such as Arrays, Linked Lists, Stacks, and Queues, the narrative progresses to intricate structures like Trees, Graphs, and Hash Tables. Practical applications in real-world scenarios are highlighted through case studies and tangible examples, offering a bridge between theory and application. The study encapsulates the dynamic essence of the field, providing insights into ongoing research and innovative trends, including the integration of machine learning and the application of bio-inspired structures. As we navigate the intricate web of Data Structures, this study seeks to unravel their significance and foster a deeper understanding of their implications in addressing contemporary computational challenges.
Keywords: advanced data structures; data structures; fundamental data structures; innovations; real-world applications; research trends